Identifikasi dan Prevalensi Cacing pada Saluran Pencernaan Ikan Salem (Scomber japonicus) di Pangkalan Pendaratan Ikan Muara Angke, Jakarta Utara [ Identification and Prevalence of Helminthic Gastrointestinal In Chub Mackerel (Scomber japonicus) in The Fish Landing Base Muara Angke, North Jakarta] - Sri Subekti; Rengga Eko Pradipta; Kismiyati Kismiyati (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract The high interest of public to Marine fish, making more request of chub mackerel (Scomber japonicus). Chub Mackerel is one commodity that has economic and high nutrient value. The Chub Mackerel obtained from the Indonesian importation from China. However, fish importation can be affected by diseases caused by helminthic endoparasites infection. The parasites that infected chub mackerel probably be caused by pollution due to environmental factors that could decreased the immune system, and making a fish easily infected by helminthic endoparasite as Anisakis. This parasite is zoonosis and could infected to human. Therefore, identification and prevalence of this parasite was needed in order to human consumed and managed this fish correctly. The purpose of this study was to identify and to know the prevalence of this helminth that infected a chub mackerel fish (Scomber japonicus) from fish importation that were sold in Fish Landing Base Muara Angke, North Jakarta. Research methodology using survey methods through sampling at locations directly. Fish samples were examined as many as 60 samples of chub mackerel. The main parameters are observed prevalence of helminth and helminth that infect in gastrointestinal chub mackerel. The result identification of helmint that infect chub mackerel descriptively analyzed and presented in the form of figures and tables. The result showed the presence of the third-stage larvae Anisakis simplex that infected the intestinal mucosa and lumen of chub mackerel fish, in Fish Landing Base Muara Angke, North Jakarta with prevalence was 70%.